S8 Do physical activity levels and PROMs improve following therapeutic aspiration of pleural effusions?. (11th November 2022) - Welch, H; Barton, E; Beech, E; Patole, S; Stadon, L; Clive, A; Maskell, N
Abstract : Patients with symptomatic pleural effusions frequently report improvement in breathlessness following therapeutic thoracocentesis (TT). The predominant patient reported outcome measure (PROM) is Visual Analogue Score for Dyspnoea (VASD). Dsypnoea-12 (D12) and Multidimensional Dyspnoea Profile (MDP) have been developed to assess multidimensional aspects of dyspnoea but remain unevaluated in pleural effusion. Objective symptom measurement in this cohort is challenging but physical activity (PA) monitoring may provide insight into patient experience. Aims: To assess D12 and MDP and record PA levels in patients with symptomatic pleural effusion before and after TT. Methods: Patients were recruited from the pleural admission avoidance clinic at North Bristol NHS Trust. Eligible patients were assessed in hospital or at home before clinic review. Baseline VASD, D12 and MDP were completed and a wrist-worn Actigraph wGT3X-BT (Actigraph Corp USA) attached then worn continuously for 5–7 days. Patients attended clinic within 48 hours and underwent TT. PROMs were repeated post-TT, and 3 days later. Results: Data has been collected on 11 patients. Mean patient age was 74.6 (SD10.7) and 64% were male. Mean pleural fluid volume removed was 1129 ml (253.7). Mean VASD difference observed was 21.3 mm (33.1) (MCID 16 mm), mean D12 score difference was 8.6 (SD 8.4) (proposed MCID 3) and mean total MDP score difference was 25.7 (SD 24.2) (mean perception score 18.0 (13.7) and mean emotion score 7.2 (12.6)). No meaningful change was observed in mean minutes spent in sedentary, light or moderate PA. However, vector magnitudes (VM) demonstrated difference between groups (pre-TT mean 846750/24 hr, post-TT mean 1308036/24 hr, two tailed t-test p=0.00027) with three patients showing clearly increased VM levels post-TT. Conclusions: In this dataset, PA monitoring showed a moderate increase in mean VM post-TT however patients remained predominantly sedentary, suggesting other factors may influence PA. VASD, D12 and MDP all report a score reduction greater than MCID following TT. The already well established VASD is a reliable tool for assessing breathlessness following pleural interventions. Further work is required to elucidate the true value of PA monitoring in pleural effusion. The D12 and MDP scores show potential for providing further insight into patient experience in this cohort. Please refer to page A208 for declarations of interest related to this abstract.